Fintech and Traditional Banking: A Bibliometric Study of Financial Innovation - Judijanto, Loso; Yulistina, Yulistina; Astutik, Wahyuni Sri; Alfiana, Alfiana (West Science Interdisciplinary Studies, 2025)
Financial technology (fintech) has emerged as a transformative force reshaping the financial industry, influencing traditional banking institutions and introducing innovative business models. This study conducts a bibliometric analysis of fintech and traditional banking research using data from Scopus and visualization through VOSviewer. The analysis explores thematic trends, key research contributions, and evolving collaborations within financial innovation. Findings reveal that fintech has transitioned from being a disruptive force to an integral component of the financial ecosystem, fostering partnerships with traditional banks. Key themes include digital banking, blockchain, artificial intelligence, financial inclusion, and regulatory challenges. The study highlights the increasing role of emerging technologies in enhancing financial services while addressing cybersecurity and compliance concerns. Global research collaboration patterns indicate a strong focus on financial inclusion and regulatory frameworks across different economies. This research provides valuable insights into the trajectory of fintech literature and identifies areas for future exploration, particularly in sustainability, AI-driven finance, and central bank digital currencies (CBDCs).